Amateur Art Discourse in the Era of Stagnation (With Reference to Art Magazines) - Suvorova, A. A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
This article considers the transformation of the amateur art discourse of the stagnation period. The research is based on critical reviews and problem articles published during the period in special art magazines. The concept of artistic and political discourse is used as a basic concept in the article. The author reveals the structure of the discourse of amateur art, which combined the stagnation period and the component of the official ideological construct, formed during the 1930s, and a more modernised language of professional art and scholarly studies. The author reveals that in the mid-1960s, specialised magazines actualised the issue of amateur creativity, using a new definition of amateur art; there emerged criticism of self-taught professionals imitating fine arts. Together with that, critical articles and reviews of foreign exhibitions demonstrated the change in the pattern of amateur art and the legitimisation by the authorities of the new artistic languages of such artists. In the late 1960s, art critics made the first attempts to comprehend the origins of naïve art, the authors contemplated primitivism and its connections with urban folklore. By the mid-1970s, art criticism and research finally legitimised naïve art and separated it from amateur art.